Through-Floor Vital Sign Searching for Trapped Person Using Wireless-Netted UWB Radars - Zhenghuan Xia (MDPI AG, 2021)
In personnel rescue applications, considerable attention has been paid to the positioning method of living persons. Especially, the effective vital sign searching is urgently required. This work presents an effective multiple-observation-points-based vital sign searching method for trapped persons using wireless-netted ultra-wideband (UWB) radars. Controlled by a wireless network, four UWB radars are connected to form a group. Based on that, we design an optimized searching path strategy and the corresponding vital sign searching procedure. The simulated result illustrates the proposed vital sign searching strategy on the spatial locations of the trapped person. Finally, the proof-of-principle through-floor experiment was also carried out, verifying the performance of this proposed vital sign searching algorithm.